2016
DOI: 10.1159/000448078
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in Posttraumatic Tremor: A Series of Cases and Literature Review

Abstract: Background: Posttraumatic tremor (PTT) is the most frequent movement disorder secondary to cranioencephalic trauma and can be persistent and disabling. Objectives: We review and assess the efficacy of deep brain stimulation (DBS) at the VIM/VOP/ZI (ventralis intermedius/ventrooralis posterior/zona incerta) complex level for the treatment of PTT. Methods: During the period from 1999 to 2014, 5 patients diagnosed with PTT were selected who had experienced a major deterioration in their quality of life without im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…VIM was selected as the target for the disabling tremor, but surprisingly we found that stimulation of VIM also attenuated the focal hand dystonia. Besides, some case reports also indicated that VIM DBS resulted in improved dystonia as well as tremor reduction.…”
Section: Discussionmentioning
confidence: 99%
“…VIM was selected as the target for the disabling tremor, but surprisingly we found that stimulation of VIM also attenuated the focal hand dystonia. Besides, some case reports also indicated that VIM DBS resulted in improved dystonia as well as tremor reduction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] The effectiveness of Vim thalamotomy has also been previously reported. [ 11 , 12 ] Moreover, recurrence after Vo thalamotomy has been reported to occur due to insufficient or incorrect coagulation over the entire Vo nucleus of the thalamus. [ 7 ] In our case, the thalamotomy lesion after the first operation did not cover a part of the Vo nucleus [ Figure 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proper management of post-traumatic tremor is limited by the lack of effectiveness of pharmacological approaches, leading to a growing interest in surgical techniques ( Mendonça et al, 2018 ; Wang et al, 2020 ). Several systematic reviews have been published on a small pool of patients in the literature – fewer than 100 to date – and have found that deep brain stimulation can be an effective therapeutic modality and can provide greater postural tremor suppression compared with medical management ( Rojas-Medina et al, 2016 ; Artusi et al, 2018 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following severe TBI, 13–66% of patients have persistent and disabling movement disorders including various combinations of tremors and dystonia ( Krauss and Jankovic, 2002 ). Stereotactic surgery is an effective form of therapy for these difficult to treat disorders with thalamotomy and deep brain stimulation (DBS) demonstrating variable but often long-term functional benefits ( Krauss and Jankovic, 2002 ; Rojas-Medina et al, 2016 ; Artusi et al, 2018 ; Mendonça et al, 2018 ). Given the variable movement disorder phenomenology in TBI, it is likely that the underlying pathophysiology involves multiple motor circuits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation